Validation of claims-based indicators used to identify flare-ups in inflammatory bowel disease. (March 2021) - Burisch, Johan; Zhang, He; Choong, Casey Kar-Chan; Nelson, David; Naegeli, April; Gibble, Theresa; Goetz, Iris; Egeberg, Alexander
Background & Aims: There are currently no validated claims-based indicators for identifying a worsening of disease in patients with inflammatory bowel disease (IBD). Therefore, we aimed to develop and validate indicators that identify flare-ups of IBD using data from Danish nationwide registries. Methods: Using Danish nationwide administrative data, we identified all patients with Crohn's disease (CD) or ulcerative colitis (UC) who had at least one measurement of faecal calprotectin between 1 January 2015 and 31 June 2017. We tested several different claims-based indicators of disease flare-ups against levels of faecal (F-)calprotectin (no flare-up: <250 mg/kg; mild flare-up: 250–1000 mg/kg; severe flare-up: ⩾1000 mg/kg). A generalised estimating equation was used to evaluate whether the proposed indicators could predict disease activity. Results: A total of 890 children and 4719 adults with CD, and 592 children and 5467 adults with UC were included in the study. During the observation period, 48–61% and 48–55% of the CD and UC patients, respectively, had no flare-up, 26–29% (CD) and 24–26% (UC) experienced a mild flare-up, and 12–23% (CD) and 21–27% (UC) experienced a severe flare-up. Combinations of indicators that could predict a flare-up in CD and UC adults included hospitalisation, surgery, initiation or switch of biological therapy, treatment with systemic steroids, locally acting steroids or topical 5-aminosalicylates, colonoscopy/sigmoidoscopy, and magnetic resonance imaging/computed tomography. In children, only the number of gastroenterology visits was significant as an indicator among UC patients, and none were seen in children with CD. Overall, the indicator combinations resulted in a predictive ability of 0.62–0.67. Conclusion: Administrative claims data can be useful for identifying patients exhibiting (F-calprotectin defined) flare-ups of their IBD. Clinically relevant events captured in the Danish national patient registry are associated with increased levels of calprotectin and hence increased disease activity, and can be used as valid outcomes in future studies.